Caracterização biogeoquímica da Lagoa de Araruama, RJ - Mello, Tatiana Baptista Martinez (2007)
The Araruama lagoon is the most hipersaline coastal lagoon of the Rio de Janeiro State and has been experienced for the last decades an intense domestic sewage load due to high tourism pressure. Since 2005 July, its clean and oligotrophic waters got dark. This work intended to evaluate the new trophic level relating recent environment changes with biogeochemistry characteristics measure through physical-chemical parameters, metabolism, nutrients, chlorophyll a and elemental and isotopic composition of the sediments. Two samples approaches were developed. The first one considered 11 sites around the lagoon at September, October and December months of 2005 year. It was considered the months with extreme values of evaporation-precipitation ratios, with positive values in October and negative values in December. The second approach considered 12 sites distributed in the limnetic region of the lagoon (2006 January). Most of the parameters analyzed in each site did not presented significant differences among months samples (ANOVA statistic analysis). Among sites sampled, significant differences were found for some of the parameters (ex. DOC, TOP and Chl a) separating sites localized near the rivers mouths from the others shore sites and by the sites in the middle of the lagoon. Higher values of the different carbon species were found mainly at the limnetic lagoon sites (DIC=95±31, DOC=24±8 e POC= 7,6±1,6 mg.L-1). Among the lagoon shore sites we found similar concentrations highlighting the TIN (37±67M) e PO4-3 (5,5±7,3M) input from the rivers Maturama and Mossoró during the rainy months. At those rivers sites higher CO2-excess characterized heterotrophic activities. At the other shore sites the metabolism was characterized with a balance among auto and heterotrophic. On the other hand, the limnetic region of the lagoon were characterized as autotrophic due to the high primary productivity. However, high carbon and chlorophyll content supported by the rivers input and by the long water renewed (T50% = 84 dias) should carry this system to present dystrophic crisis. Due to recent human changes during recent decades around the lagoon drainage basin, it was evident a trophic level change from oligotrophic to hipertrophic (C/N/PMARGIN = 603/37/1 e C/N/PCENTER = 941/57/1). Those changes increased the sediments nutrient cycles, growing the primary productivity in the water column and decrease the benthonic productivity due to the less luminosity. Finally, the Araruama lagoon was characterized from an increase in the biogenic elements budgets of the water column and sediment compartments. It demonstrate a narrow relationship between the high organic matter input in a restricted lagoon that has already been experienced a eutrophication process. The results from this work highlight the necessity of future research to deal with the impacts of the effluent loads, the necessity of the ocean-channel drainage, the assessment of the water quality variability and mainly with an estimative of lagoon water renew measure through organic matter fluxes from the lagoon to the ocean.